Acute Myocardial Infarction in Snake bite Envenomation A Case Report (Journal of Medicine, 2015)
Snake bite envenomation is a common problem in tropical countries, especially in rural parts of India. We came across a 30 year old male who presented to the hospital after 4 hours with history of Russells viper snake bite developing acute non ST elevation myocardial infarction (MI). Myocardial infarction was confirmed by history of left sided chest pain radiating to left arm with diaphoresis and electrocardiographic changes with increased serum troponin levels. Myocardial infarction is a rare complication of snake bite hence case report.DOI: http://dx.doi.org/10.3329/jom.v16i1.22401 J MEDICINE 2015; 16 : 46-47